Friction and wear of selected metal ceramic and polycrystalline diamond sliding couples - Damn, Oliver Frank Rudolf August (My University, 2017)
This thesis describes a study of the friction and wear characteristics of a range of oxide and silicon-based ceramics sliding against AlSI 440C stainless steel, as well as various sliding combinations of two types of De Beers polycrystalline diamond (PCD), namely Syndite and Syndax, To facilitate the former work, a high-speed reciprocating sliding test machine with computerized data acquisition and control was developed. It was confirmed that under water-lubricated sliding, the oxide ceramics (alumina, PSZ, 3YTZP, and Ce-TZP) showed higher friction coefficients and Weal' rates than the silicon-based ceramics (Sialon and silicon nitride). This was related to different levels of adhesion and the formation of metallic transfer films. For the zirconia ceramics, increased transformation toughening was associated with increased surface fracture damage and metallic film formation. In general, the metallic transfer films were beneficial, protecting the underlying ceramic and dominating the friction and wear behaviour. The superior performance of the silicon-based ceramics was related to the formation of lubricious tribofilms containing silicon oxides and hydroxides. Experiments with synthetic mine water as lubricant demonstrated that the presence of significant amounts of chloride and sulphate in the water generally reduced friction and wear. This was tentatively explained in terms of reduced adhesion and the promotion of iron oxide and hydroxide formation. It is suggested that the influence of sulphate may be more important in thi'3 regard than that of chloride. The tribological behaviour of self-mated Syndite PCD sliding couples is dominated by the formation of Co-rich trlbofilms, which nrc associated with increased friction coefficients and reduced load carrying capacity (LCC). Syndax, which employs silicon as the binder phase, shows lower friction coefficients anti higher LCe under both dry and water-lubricated sliding conditions. Mixed Syndax/Syndite couples show superior performance to self-mated Synditc tinder dry sliding conditions, but 110 improvements in the presence of water. The former effect is related to the preferential removal of Co 11'0111 the Syndite surface to the Syndax
A thesis submitted to the Faculty of engineering. University of Witwatersrand. Johannesburg, in fulfilment of the requirements for the Degree of Doctor of Philosophy Pretoria, 1995
Keywords: Ceramic metals; Silicon compounds; Friction; Tribology; Diamonds, Artificial; Diamonds, Industrial